Has Liberalization Strengthened the Link between Services and Manufacturing? - Christine Marie Liao; Gloria O. Pasadilla (Philippine Institute for Development Studies (PIDS), 2007)
Globalization and pressure from increased competition have led to splintering of in-house services from formerly integrated manufacturing firms in developed economies and, at the same time, to an increase in outsourcing of these same services. These two trends have caused a stronger linkage in services and manufacturing in economic data because services which were previously lumped with manufacturing are now recorded separately and, in a sense, given identity. The study tries to shed some light on this linkage in the Philippine case. Contrary to experiences of other countries, the contribution of services to growth in manufacturing decreased from the 1980s to the 1990s. The manufacturing sectors usage of services also declined from the first to the second period. This result suggests that the Philippines has caught the splintering trend quite late and is, perhaps, only now catching on that the available 1990s data have not yet been able to capture.
Keywords: 330; globalization; splintering; outsourcing; services-manufacturing link; growth accounting; Globalisierung; Outsourcing; Wirtschaftswachstum; Systemtransformation; Branchenentwicklung; Industrie; Dienstleistungssektor; Schätzung; Philippinen